(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Starting from December 2019 novel COVID-19 pandemics has become major challenge not only to healthcare community but also livelihood of humans. Exponential and uncontrollable spread of life-threatening viruses becomes a serious issue for the governments of all the countries across the globe. Unfortunately, to stop the further spread of the virus most nations suddenly announced strict lockdown for several days. The lockdown situation was very panic and affected adversely on livelihood of human beings. The adverse effect was dramatically more in unorganized sector than the people working in organized sectors. Lack of literacy, awareness and government policies are the major reasons behind this. In this paper, we present the detailed analytical study of the impact of COVID 19 on livelihood of unorganized sector in India. India is developing country, and it has wide range of unorganized sector laborers. The primary data was collected from the laborers directly through questionnaires. By confirming the result of this analytical study, livelihood of unorganized sector affected adversely. Government and NGOs should make extra efforts to frame policies and laws to uplift their lives. The paper will come up with some technological measures to identify and help such unorganized laborers in any kind of community issues to fulfill their basic requirements.